Implementasi Perpanjangan Masa Angsuran Pembiayaan Murabahah di Bank Syariah pada Masa Pandemi Covid-19 - Putri Nazli (FEB Universitas Maritim Semarang, 2024)
The Covid-19 pandemic has occurred. Since 2019, almost all countries in the world have experienced it. The Indonesian population is experiencing a pandemic that causes millions of people to experience difficulties, one of which is economic factors, namely in paying off debt or murabaha financing at Islamic banks and conventional banks. This is due to a decrease in daily income. If these conditions are not addressed properly, it will result in a decline in the economic growth of a country. This article aims to examine the application of the Qur'an Surah Al Baqarah verse 280 to the gift of restructuring murabahah financing to customers affected by the Covid-19 pandemic. The researcher used the literature review method. In addition, this study also uses a narrative analysis method to describe the reality that occurs in the field and conducts interviews with customers and the Bank. The research study conducted in this article shows that the application of Surah Al Baqarah verse 280 during the Covid-19 pandemic can be a solution to maintain the level of economic growth in Indonesia.